Can Use Simple Messages Information to Make a Remuneration Profit? -Evidence from Taiwan Stocks - Hsiao, Chien-Wen (International Journal of Finance, 2022)
Purpose: The goal of this research is to use the correlation analysis method (CAM) to find out the investors can invest with simple messages. Results: This research's empirical results indicate the following: (1) Based on our empirical results obtained from using the correlation analysis method (CAM) method, the highest price, lowest price, and closing price can affect the opening price, and there is a significant and positive relationship. Moreover, the stock trading volume is an insignificant positive correlation, and the rate of price spread is an insignificant negative correlation. (2) This research assumes no external interference and government protection. And that stock investors do not have any technical analysis and other conditions. Whether the company can make a profit can reflect the value of bonds and stocks through public information. Therefore, investors can invest based on simple information. The grey relational analysis (GRA) research shows that that both the highest price and the lowest price displays were significant. The closing price was strong. In contrast, the study found that the stock trading volume and price spread displays are weak, and the analysis results showed almost no effect. Unique contribution to theory, policy and practice: Therefore, if you play day trader it is feasible to use the high and low stock prices to make a remuneration profit.